Natural killer cells in multiple sclerosis: foe or friends? - Fatemeh Aghaee; Mohammadreza Abedinpour; Saeid Anvari; Alia Saberi; Amir Fallah; Arash Bakhshi (Frontiers in Cellular Neuroscience)
Multiple sclerosis (MS) is an immune-mediated disorder involving the central nervous system (CNS), in which demyelination is caused. The initiation and progression of MS is thought to depend largely on CD4+ T lymphocytes, yet new data has emphasized the involvement of the innate immune system in the MS disease responses. Generally, several types of immune cells play a part, with natural killer (NK) cells being essential. Different subsets of natural killer cells function differently within the course of an autoimmune disease, such as MS. There are mainly two types of natural killers in humans: immature CD56bright CD16– and mature CD56dim CD16+ natural killers, together with their respective subtypes. Factors from natural killers expand the T cell population and control the process by which native CD4+ T cells differentiate into Th1 or Th2 lymphocytes, which affect autoimmune responses. Natural killer subsets CD56bright and CD56dim may have differing roles in MS development. The impact of these NK cell subsets is influenced by factors such as Granzymes, genetics, infections, TLR, and HSP. We reviewed and evaluated the relationship between natural killer cells and MS.